Pengaruh Beban Kerja Terhadap Kinerja Karyawan Pada Generasi Z di Pizza Hut Kota Samarinda - Rusty, Atnin Sintania Aprilla; Efendi, Achmad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of workload on the performance of Generation Z employees at Pizza Hut outlets in Samarinda City. The formulation of the problem in this study is whether workload has an influence on the performance of Generation Z employees. The research method used is quantitative with a positive approach. The data collection technique was carried out through distributing questionnaires to Generation Z employees at Pizza Hut Samarinda outlets. Data analysis using simple linear regression test to see the influence between workload on employee performance. The results showed that workload had a positive and significant effect on the performance of Generation Z employees. A balanced workload can encourage improved performance, but too much load often tends to reduce productivity and cause stress. The conclusion of this study is that proportional workload management is important to maintain and improve employee performance, especially for Generation Z who are still in the adaptation stage to the world of work.